Sex differences in asthma control, lung function and exacerbations: the ATLANTIS study - Salman Siddiqui; Thys van der Molen; Huib A M Kerstjens; Dave Singh; Chris Brightling; Maarten van den Berge; Alberto Papi; Klaus F Rabe; Leonardo M Fabbri; Monica Kraft; Martijn C Nawijn; Susan Muiser; et al. (BMJ Open Respiratory Research, 2024)
Background Asthma is a heterogeneous disease with a prevalence and severity that differs between male and female patients.Question What are differences between male and female patients with asthma with regard to asthma control, lung function, inflammation and exacerbations?Methods We performed a post hoc analysis in the ATLANTIS (Assessment of Small Airways Involvement in Asthma) study, an observational cohort study including patients with asthma from nine countries with a follow-up of 1 year during which patients were characterised with measures of large and small airway function, questionnaires, inflammation and imaging. We compared differences in baseline characteristics and longitudinal outcomes between male and female patients with asthma.Results 773 patients were enrolled; 450 (58%) of these were female. At baseline, female patients with asthma were in higher Global Initiative for Asthma (GINA) steps (p=0.042), had higher Asthma Control Questionnaire 6 (F: 0.83; M: 0.66, p<0.001) and higher airway resistance as reflected by uncorrected impulse oscillometry outcomes (ie, R5-R20: F: 0.06; M: 0.04 kPa/L/s, p=0.002). Male patients with asthma had more severe airway obstruction (forced expiratory volume in 1 s/forced vital capacity % predicted: F: 91.95; M: 88.33%, p<0.01) and more frequently had persistent airflow limitation (F: 27%; M: 39%, p<0.001). Blood neutrophils were significantly higher in female patients (p=0.014). With Cox regression analysis, female sex was an independent predictor for exacerbations.Interpretation We demonstrate that female patients are in higher GINA steps, exhibit worse disease control, experience more exacerbations and demonstrate higher airway resistance compared with male patients. The higher exacerbation risk was independent of GINA step and blood eosinophil level. Male patients, in turn, have a higher prevalence of persistent airflow limitation and more severe airflow obstruction. These findings show sex can affect clinical phenotyping and outcomes in asthma.Trial registration number NCT02123667.